Bibliometric analysis of research trends in relationship between sarcopenia and surgery - Liu, Tao; Song, Fengjing; Su, Deqiang; Tian, Xiaofeng (Frontiers in Surgery, 2023)
Background: The relationship between sarcopenia and surgery has attracted an increasing number of researchers in recent years. Our study aimed to identify the current research hotspot and status in this field by using bibliometric and visualization analysis. Methods: Publications about the relationship between sarcopenia and surgery that met the inclusion criteria were collected from the Science Citation Index Expanded. The bibliometric and visualized studies were performed using VOSviewer, and R. Results: A total of 2261 documents on the relationship between sarcopenia and surgery were included in our study. These articles were written by 13757 authors from 2703 institutions in 70 countries and were published in 772 journals. The USA is the most productive and influential country in this field (524 publications and 15220 citations). The Udice French Research Universities was the most productive institution in this field (57 publications), and the University of Alberta had the largest number of citations. Annuals of Surgical Oncology published the most studies in this field. Shen Xian was the most productive author in this field (number of publications = 19), and Baracos Vickie was the most influential author, whose studies in this field had been cited 2209 times. The cluster analysis was performed and shown in Figure 4C. Keywords were classified into 6 clusters: Cluster 1 (body composition and nutrition), Cluster 2 (sarcopenia), Cluster 3 (malnutrition and cachexia), Cluster 4 (cancer surgery), Cluster 5(elderly and frailty), Cluster 6 (neuromuscular scoliosis). Conclusion: The relationship between sarcopenia and surgery was still a controversial and well-discussed topic in recent years. Our study showed that the study in this field mainly focused on sarcopenia, oncology surgery, orthopedics, and nutrition.